Teleología en la constitución del otro - Uceda Puertas, Bruna (2020)
This presentation aims to discuss the experience of empathy in regards to the notion of teleology in Edmund Husserl’s transcendental phenomenology. With this in mind, it briefly looks to describe the teleology present in the constitution of meaning and validity in cognitive acts in general, making reference to the phenomenological analysis of perception. Then, it wishes to discuss the particularity of this teleological movement in the cognitive experience of the other, insofar as it involves non-originary evidence. Following Husserl’s instructions, we begin approaching this empathic experience beginning with the static analysis of the experience of the transcendental other to then discuss the genetic analysis of the mundane other.